Covenantal Nomism and the Gospel of Matthew - Park, Eung Chun (The catholic biblical quarterly, 2015)
In this article, I examine whether the notion of covenantal nomism is applicable to the Gospel of Matthew. I survey several key concepts of covenantal nomism in Matthew to see how they function in the presentation of the story of Jesus. Then I discuss two equally binding terms in Matthew's soteriology: Torah and its hermeneutics by Jesus. I will show how Matthew significantly alters the terms of covenantal nomism and articulates a soteriology that is still thoroughly anchored in Jewish roots and yet distinctively shaped by the teaching of Jesus.